EXTENDING PROTECTION MOTIVATION THEORY FOR ORGANIZATIONAL CYBERSECURITY BEHAVIOR: A SYSTEMATIC LITERATURE REVIEW - Susyanto, Susyanto; Mulyanti, Rita Yuni; Rini, Nova (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2026)
This study systematically synthesizes and critically evaluates the application of Protection Motivation Theory (PMT) in explaining organizational cybersecurity behavior, addressing conceptual fragmentation in prior research through the integration of protection habit and cybersecurity awareness into an extended PMT framework. A Systematic Literature Review (SLR) was conducted in accordance with PRISMA 2020 guidelines, drawing on peer-reviewed studies published between 2015 and 2025 retrieved from Scopus-indexed and major academic databases using structured Boolean search strategies. Following duplicate removal, screening, and full-text eligibility assessment, 35 studies were included and analyzed through thematic and narrative interpretative synthesis. The findings indicate that coping appraisal particularly self-efficacy consistently exerts a stronger influence on cybersecurity behavior than threat appraisal. However, sustainable compliance is reinforced by protection habits and cognitively mediated by cybersecurity awareness, suggesting that PMT functions as a dynamic motivational system rather than a static cognitive model. The study contributes theoretically by reconceptualizing protection habit as a behavioral reinforcement mechanism and cybersecurity awareness as a translational mediator within the PMT structure, thereby proposing an integrative behavioral-system model to enhance theoretical coherence and contextual applicability in organizational cybersecurity research.